2022
DOI: 10.4103/jfmpc.jfmpc_1043_22
|View full text |Cite
|
Sign up to set email alerts
|

Adverse drug reactions reporting: Five years analysis from a teaching hospital

Abstract: A BSTRACT Background: Adverse drug reactions (ADRs) are important cause of morbidity and mortality. Despite its known importance, rate and quality (completeness score) of ADR reporting is not satisfactory. The objective of this study was to analyze pattern and completeness score of ADRs during past five-years. Material and Methods: In this retrospective study, ADRs reported between 2017 to 2021 were analyzed according to year, gender, age-grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
0
0
0
Order By: Relevance
“…Anti-infective agents, followed by blood and blood-forming agents, and musculoskeletal system medications were the most commonly reported ATC classes. These findings were consistent with previous studies conducted in Jordan (Alsbou et al, 2017 ), Ethiopia (Thakare et al, 2022 ), and Saudi Arabia (Yousef et al, 2022 ). However, studies from other countries like Germany have reported nervous system agents as the primary contributors to ADR reporting or hospitalisation (Li et al, 2021 ; Thomas et al, 2022 ).…”
Section: Discussionsupporting
confidence: 93%
“…Anti-infective agents, followed by blood and blood-forming agents, and musculoskeletal system medications were the most commonly reported ATC classes. These findings were consistent with previous studies conducted in Jordan (Alsbou et al, 2017 ), Ethiopia (Thakare et al, 2022 ), and Saudi Arabia (Yousef et al, 2022 ). However, studies from other countries like Germany have reported nervous system agents as the primary contributors to ADR reporting or hospitalisation (Li et al, 2021 ; Thomas et al, 2022 ).…”
Section: Discussionsupporting
confidence: 93%